2022
DOI: 10.1109/lra.2022.3183799
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Biomechanical Effects of Providing Adaptive Assistance With an Ankle Exoskeleton in Individuals After Stroke

Abstract: Recent studies on ankle exoskeletons have shown the feasibility of this technology for post-stroke gait rehabilitation. The main contribution of the present work is a comprehensive experimental analysis and protocol that focused on evaluating a wide range of biomechanical, usability and users' perception metrics under three different walking conditions: without exoskeleton, with an ankle exoskeleton unpowered, and with an ankle exoskeleton powered. To carry out this study, we developed the ABLE-S exoskeleton t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…1.A). Previous experiments in stroke survivors showed relevant benefits of the ABLE-S exoskeleton to improve spatial and temporal gait parameters [9]. Specifically, we found that walking with the ABLE-S reduced abrupt loading responses, foot drop, hip compensatory movements and asymmetrical gait patterns compared to walking with no exoskeleton.…”
Section: The Able-s Exoskeletonsupporting
confidence: 50%
See 2 more Smart Citations
“…1.A). Previous experiments in stroke survivors showed relevant benefits of the ABLE-S exoskeleton to improve spatial and temporal gait parameters [9]. Specifically, we found that walking with the ABLE-S reduced abrupt loading responses, foot drop, hip compensatory movements and asymmetrical gait patterns compared to walking with no exoskeleton.…”
Section: The Able-s Exoskeletonsupporting
confidence: 50%
“…The ABLE-S device [9] is a unilateral ankle exoskeleton that provides PF and DF assistance to increase forward propulsion and foot clearance in hemiplegic individuals (see Fig. 1.A).…”
Section: The Able-s Exoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since they are commonly connected to gearboxes with large velocity transmission ratios, the rotary inertia of devices is large; it curbs free foot motion. Accordingly, motors with large output torque and low rotary velocity 24 can effectively limit their inertia levels.…”
Section: Design Factorsmentioning
confidence: 99%
“…Results indicated that the identified assistance timing improved the activity of the tibialis anterior. de Miguel-Fernandez et al 24 designed assistive torque profiles for PF and DF assistance, with adjustable timing and level following a pi-shaped function. Wu et al 92 conceived assistive torque for an ankle exoskeleton based on timing during a gait cycle.…”
Section: Control Technologiesmentioning
confidence: 99%